Strategi Menciptakan Budaya Literasi di MTsN 10 Tanah Datar - Nemi Refriyanti; Sirajul Munir; Demina Demina; Annisaul Khairat (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The purpose of this research is to reveal the strategy of the madrasa principal in seeking an educated academic environment at MTsN 10 Tanah Datar. This type of research is qualitative research with a case study approach. The research location is at MTsN 10 Tanah Datar. There were 6 research informants, namely school principals, curriculum representatives, public relations representatives, teachers, librarian heads, and students at MTsN 10 Tanah Datar. Data collection techniques used are through interviews, observation and documentation. The technique of data analysis is by means of triangulation, namely triangulation of sources and triangulation of techniques. The results of the study show that the Madrasah Principal's strategy in creating a Literacy Culture at MTsN 10 Tanah Datar is to strive for a literate academic environment with a). Planning literacy activities, namely creating literacy programs and forming a solid work team. B). Implementation of literacy activities, namely encouraging activities that smell of literacy, involving students to diligently read every day, enlivening the literacy corners of the madrasa, providing motivation to write to all madrasa residents to synergize, cooperate, and set an example. C). Evaluation of literacy activities, namely monitoring and follow-up.